2010
DOI: 10.2166/wpt.2010.020
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of lead ion biosorption from aqueous solution onto lyophilized Aspergillus niveus

Abstract: The biosorption of lead ions (Pb2+) onto lyophilized fungus Aspergillus niveus was investigated in aqueous solutions in a batch system with respect to pH, contact time and initial concentration of the ions at 30 °C. The maximum adsorption capacity of lyophilized A. niveus was found to be 92.6 mg g−1 at pH 5.1 and the biosorption equilibrium was established about in 30 min. The adsorption capacity obtained is one of the highest value among those reported in the literature. The kinetic data were analyzed using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…produce spherical mycelia which help in metal accumulation (Prasenjit and Sumathi 2005 ). Karaca et al ( 2010 ) reported that maximum Pb biosorption was occurred at pH 5 by A. niveus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…produce spherical mycelia which help in metal accumulation (Prasenjit and Sumathi 2005 ). Karaca et al ( 2010 ) reported that maximum Pb biosorption was occurred at pH 5 by A. niveus.…”
Section: Discussionmentioning
confidence: 99%
“…Up to best of our knowledge A. niveus is firstly isolated from tannery effluent and there is no report available on A. niveus for chromium removal and tannic acid degradation. However one report on Pb removal is available (Karaca et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…were observed to be the most commonly occurring in the heavy metal contaminated soils as also reported by Ahmad et al [21] and Zafar et al [23]. Several Aspergillus species have been used for heavy metal ion adsorption such as A. niger [24], A. fumigatus [25], A. niveus [26], A. versicolor [27], A. flavus [28], A. terreus [29] and A. cristatus [30] etc. Sen and Ghosh Dastidar [31] have also studied Aspergillus sp.…”
Section: Resultsmentioning
confidence: 80%
“…Therefore, there is a requirement of an effective and affordable biological method for the removal of lead from the electronic waste 8 . Now-a-days biosorption technique is receiving attention in the removal of toxic metals from waste 9 as it is non-polluting, highly selective, more efficient and cost effective for treatment of large volumes of wastewaters containing low metalconcentrations 10,11 . Biosorption is the ability of biological materials like bacteria, algae, fungi, yeasts to adsorb heavy metals from waste through uptake 12 .…”
Section: Introductionmentioning
confidence: 99%